Central memory phenotype drives success of checkpoint inhibition in combination with CAR T cells. Issue 7 (25th April 2020) - Toews, Karin; Grunewald, Laura; Schwiebert, Silke; Klaus, Anika; Winkler, Annika; Ali, Solin; Zirngibl, Felix; Astrahantseff, Kathy; Wagner, Dimitrios L.; Henssen, Anton G.; Deubzer, Hedwig E.; Schulte, Johannes H.; et al.
Abstract: The immunosuppressive microenvironment in solid tumors is thought to form a barrier to the entry and efficacy of cell‐based therapies such as chimeric antigen receptor (CAR) T cells. Combining CAR T cell therapy with checkpoint inhibitors has been demonstrated to oppose immune escape mechanisms in solid tumors and augment antitumor efficacy. We evaluated PD‐1/PD‐L1 signaling capacity and the impact of an inhibitor of this checkpoint axis in an in vitro system for cancer cell challenge, the coculture of L1CAM‐specific CAR T cells with neuroblastoma cell lines. Fluorescence‐activated cell sorting‐based analyses and luciferase reporter assays were used to assess PD‐1/PD‐L1 expression on CAR T and tumor cells as well as CAR T cell ability to kill neuroblastoma cells. Coculturing neuroblastoma cell lines with L1CAM‐CAR T cells upregulated PD‐L1 expression on neuroblastoma cells, confirming adaptive immune resistance. Exposure to neuroblastoma cells also upregulated the expression of the PD‐1/PD‐L1 axis in CAR T cells. The checkpoint inhibitor, nivolumab, enhanced L1CAM‐CAR T cell‐directed killing. However, nivolumab‐enhanced L1CAM‐CAR T cell killing did not strictly correlate with PD‐L1 expression on neuroblastoma cells. In fact, checkpoint inhibitor success relied on strong PD‐1/PD‐L1 axis expression in the CAR T cells, which in turn depended on costimulatory domains within the CAR construct, and more importantly, on the subset of T cells selected for CAR T cell generation. Thus, T cell subset selection for CAR T cell generation and CAR T cell prescreening for PD‐1/PD‐L1 expression could help determine when combination therapy with checkpoint inhibitors could improve treatment efficacy.